Teacher Self-Efficacy and Organizational Citizenship Behavior as Predictors of Teacher Performance in Public Vocational Schools: Evidence from Mataram City, Indonesia - Nasrullah Nasrullah; Aloysius Ajab Amin; Hasim Hasim (International Journal of Management Science, 2026)
Teacher performance remains a central concern in vocational education because teachers are expected to translate technical curricula, classroom management, assessment, and student guidance into measurable learning outcomes. This study examined the effects of teacher self-efficacy and organizational citizenship behavior (OCB) on the performance of civil-servant teachers in public vocational schools in Mataram City, Indonesia. A quantitative ex post facto design was applied to a population of 354 teachers, from which 200 respondents were selected using proportional sampling based on Slovin's formula. Data were collected using structured Likert-scale questionnaires and analyzed through descriptive statistics, reliability testing, classical assumption testing, simple linear regression, and multiple linear regression. The results show that teacher self-efficacy positively and significantly predicted teacher performance (B = 0.129, t = 11.113, p = 0.003; adjusted R2 = 0.741). OCB also positively and significantly predicted teacher performance (B = 0.298, t = 9.541, p = 0.001; adjusted R2 = 0.408). When self-efficacy and OCB were entered simultaneously, the regression model remained significant (F = 22.922, p = 0.006; adjusted R2 = 0.619), indicating that personal efficacy beliefs and extra-role organizational behavior jointly explain a substantial proportion of teacher performance. These findings suggest that improving vocational-school teacher performance requires interventions that strengthen teachers' instructional confidence while also building a collaborative, prosocial, and school-supportive professional culture. The study contributes to educational management literature by integrating personal and organizational-behavioral predictors of teacher performance in a vocational-school context.